Evidence of long-term NAO influence on East-Central Europe winter precipitation from a guano-derived δ(15)N record - Cleary, Daniel M. (Sci Rep, 2017)
Currently there is a scarcity of paleo-records related to the North Atlantic Oscillation (NAO), particularly in East-Central Europe (ECE). Here we report δ(15)N analysis of guano from a cave in NW Romania with the intent of reconstructing past variation in ECE hydroclimate and examine NAO impacts on winter precipitation. We argue that the δ(15)N values of guano indicate that the nitrogen cycle is hydrologically controlled and the δ(15)N values likely reflect winter precipitation related to nitrogen mineralization prior to the growing season. Drier conditions indicated by δ(15)N values at AD 1848–1852 and AD 1880–1930 correspond to the positive phase of the NAO. The increased frequency of negative phases of the NAO between AD 1940–1975 is contemporaneous with higher δ(15)N values (wetter conditions). A 4‰ decrease in δ(15)N values at the end of the 1970’s corresponds to a strong reduction in precipitation associated with a shift from negative to positive phase of the NAO. Using the relationship between NAO index and δ(15)N values in guano for the instrumental period, we reconstructed NAO-like phases back to AD 1650. Our results advocate that δ(15)N values of guano offer a proxy of the NAO conditions in the more distant past, helping assess its predictability.